PELATIHAN PEMBUATAN KOLAM TERPAL UNTUK BUDIDAYA IKAN SISTEM RESIRKULASI BIOFLOK DI DESA GONDANG, KECAMATAN GANGGA, KABUPATEN LOMBOK UTARA - Abidin, Zaenal; Setyono, Bagus Dwi Hari; Mandalika, Eka Nurminda Dewi (Universitas Mataram, 2025)
Fish farming technology is progressively advancing in the techniques utilized and the rearing media. A tarpaulin tank is reasonably simple and inexpensive. Therefore, it is suitable for those seeking to cultivate fish with constrained land and financial resources. This project aims to train the stakeholders - in this case, members of the